The musical characteristics of Qiang songs in Wenchuan County, Sichuan Province, China (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is from the study of "Qiang songs in Wenchuan county, Sichuan province, China". This article takes the Qiang songs in Sichuan Province as the research object. The goal of this article is to analyze the characteristics of the music elements of the Qiang songs by using qualitative research methods based on field investigations. The conclusions of this article are as follows: 1) Further analysis of the melody characteristics of Qiang songs. 2) The characteristics of the rhythm and beat changes of the Qiang songs are further analyzed. 3) The tunes of the Qiang songs are analyzed. 4) The singing method of the Qiang songs needs further analysis.